Characterization of Glaucoma Medication Adherence in Kaiser Permanente Southern California. Issue 1 (January 2016) - Jones, Jason P.; Fong, Donald S.; Fang, Ervin N.; Mesirov, Claire A.; Patel, Vaishali
Abstract : Purpose: To describe adherence to glaucoma medications. Patients and Methods: Medication adherence was investigated using the computerized records of Kaiser Permanente Southern California, a group model health maintenance organization that provides care to 3.4 million residents of Southern California. Eligible glaucoma patients were diagnosed between 2005 and 2009 and had medical and prescription drug coverage between 2005 and 2009. Utilization and adherence parameters were calculated for each of the 5 years from the incident date. Results: A total of 17, 943 newly diagnosed glaucoma patients were identified between the years 2005 and 2009. Of patients diagnosed with glaucoma in 2005, 71% were continuously eligible for 5 years. Medication adherence was calculated using a medication possession ratio. Adherence was bimodal and not normal in distribution. Overall, the mean age of the entire group was 66 years, with 56% being 65 years of age or older. The high adherence group tended to be older, more likely to be female, and more likely to be white. The low adherent group (younger) tended to have more and worse diabetes, renal disease, myocardial infarction, and stroke. Conclusions: The shape of the adherence distribution appears bimodal, so analysis based on parametric measures may not be appropriate. Investigations of adherence should probably be performed separately for the low, mid, and high groups.